Economic Analysis of Cocoa Production Cropping Pattern in Nigeria, West Africa - Oladokun, Yetunde Olasimbo Mary; Oluyole, Kayode A.; Akinpelu, Ayode O.; Orisasona, Taiwo (Indonesian Coffee and Cocoa Research Institute, 2023)
Cocoa is the most prominent export crop in Nigeria in terms of its production and export capacities. There is dearth of literature on the profitability of the different cropping systems. This study therefore examined the profitability of the different cocoa cropping systems and the factors that affect the revenue of cocoa farmers for each of the cropping systems. The study area was Nigeria and information were collected from one hundred and eighty farmers using well-structured question- naires. Descriptive statistics, budgetary analysis and linear regression were used for analysis in this study. The study revealed that twenty-seven farmers practised sole cocoa cropping, seventy-five farmers practised cocoa/arable cropping and seventy-eight farmers practised cocoa/tree cropping systems, respectively. The mean age of farmers in sole cocoa cropping system was 49.3 years, for cocoa/ arable cropping system the mean age was 47.8 years while for cocoa/tree cropping system the mean age of farmers was 47.2 years. For sole cocoa cropping system, the total cost (TC) was USD 7,764; the gross revenue (GR) was USD 43,774 with USD 36,009 as profit made from the cropping system. The TC for cocoa/tree cropping system in Nigeria was USD 18,003, GR was USD 124,104 and the profit was USD 106,102. Similarly for cocoa/arable cropping system, the TC was USD 16,215, GR was USD 109,849 and profit was USD 93,634. The determinants for the three cocoa cropping systems were age, gender, marital status (married), educational level (primary), cost of seedling, cost of fertilizer, cost of fungicide, cost of herbicide, labour cost for bush clearing, land preparation, weeding and planting. Cocoa/tree and cocoa/arable cropping systems were more profitable than sole cocoa cropping systems. However, cocoa/ tree cropping system was more profitable with a value of USD 106,102.